A method for rapidly preparing a sers substrate of high loading gold nanorods and a method for using the same
Patent Information
- Application Number
- CN202610941086.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-27
- Publication Date
- 2026-08-28
AI Technical Summary
[0004]现有技术中,公开号CN118688176A的专利文件制备的基底自组装的量较少,实际放大效果有限;公开号CN112881360A的专利文件制备的基底,因PVDF膜表面不平整,不同位置的拉曼信号会有所差异,一致性较差;公开号CN113834804B的专利文件制备的基底是将金纳米颗粒过滤截留在制备好的二醋酸纤维素薄膜上,之后使用滴加测试或者过滤富集,此方法富集效果难把控,测试稳定性、重复性有待提升
1、使用MCH充当粘接剂,形成PVDF-MCH-AuNRs三明治结构,增大基底负载量;采用等离子体清洗催化技术,高效去除PVDF上杂质,催化MCH粘接基底并连接到AuNRs上;相比其他的复杂表面镀膜、多步修饰方法,本法步骤简单,单次批量制备、原料廉价;并且制备的SERS基底AuNRs负载量多,拉曼放大位点多,通过AuNRs放大拉曼信号,大幅度提高拉曼测试的信号强度并减少了荧光背景的干扰。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This application relates to the field of spectroscopic detection methods, and more specifically, it relates to a method for rapidly preparing a SERS substrate with highly loaded gold nanorods and its application. Background Technology
[0002] Surface-enhanced Raman spectroscopy (SERS) is a molecular structure characterization method based on the Raman effect and nanotechnology. Surface plasmon resonance (SPR) generated by noble metal nanomaterials such as gold and silver can amplify Raman molecular signals adsorbed on the SERS substrate by approximately 10⁶–10¹⁴ times, and in some cases, even achieve single-molecule detection. Compared to other analytical methods, SERS technology offers advantages such as not requiring complex sample pretreatment, high sensitivity and specificity, immunity to water interference, and the ability to perform rapid on-site detection.
[0003] Plasma cleaning technology involves introducing a small amount of process gas (such as hydrogen, argon, nitrogen, or a mixture thereof) and then applying a high-frequency electric field to accelerate electrons in the gas molecules, giving them extremely high energy. These high-energy electrons collide with gas molecules / atoms, causing them to ionize (lose electrons), thus generating a mixture of various particles, including high-energy free electrons, positive ions, neutral atoms / molecules, and highly reactive free radicals. Plasma technology can break down and volatilize contaminants, and free radicals can attach to the material surface, altering its chemical properties. While cleaning the sample surface, it also introduces polar groups such as hydroxyl (-OH) and carboxyl (-COOH) groups, achieving surface "activation."
[0004] In the prior art, the substrate prepared by patent document CN118688176A has a relatively small amount of self-assembled material, resulting in limited actual amplification effect; the substrate prepared by patent document CN112881360A has poor consistency due to the uneven surface of the PVDF film, which causes differences in Raman signals at different locations; the substrate prepared by patent document CN113834804B involves filtering and trapping gold nanoparticles on the prepared cellulose diacetate film, followed by drop addition testing or filtration enrichment. However, the enrichment effect of this method is difficult to control, and the stability and repeatability of the test need to be improved.
[0005] Therefore, how to prepare a new SERS substrate with the advantages of high gold nanorod loading, stable loading, and fast loading speed to enhance Raman signals and reduce fluorescence background interference is an urgent problem to be solved. Summary of the Invention
[0006] To prepare a novel SERS substrate with the advantages of high gold nanorod loading and rapid gold nanorod loading, which can enhance the Raman signal of the SERS substrate and reduce fluorescence background interference, this application provides a method for rapidly preparing a SERS substrate with high gold nanorod loading and its application method.
[0007] In a first aspect, this application provides a method for rapidly preparing a SERS substrate with highly loaded gold nanorods, employing the following technical solution: A rapid method for preparing SERS substrates with highly loaded gold nanorods includes the following steps: S1. Gold seeds were prepared by compounding citric acid, hexadecyltrimethylammonium bromide and chloroauric acid, and then crude gold nanorods were prepared by gold seed synthesis and purified to obtain gold nanorods; S2. The polyvinylidene fluoride membrane is activated with ethanol and cleaned by plasma to obtain a pretreated membrane layer. S3. Load 6-mercapto-1-hexanol and gold nanorods onto the surface of the pretreated film, and then dry it to obtain the finished product.
[0008] By employing the above technical solution, a compound of citric acid, hexadecyltrimethylammonium bromide, and chloroauric acid is used to create negatively charged citrate ions on the surface of the prepared gold nanorods, giving them a negative charge. After ethanol activation treatment, the polyvinylidene fluoride (PVDF) membrane changes from hydrophobic to hydrophilic, and the negative inductive effect of the -CF groups on the PVDF membrane is activated, resulting in a positive charge. Under electrostatic forces, the positively charged PVDF membrane and the negatively charged gold nanorods attract and connect with each other, causing the gold nanorods to adhere uniformly and densely. On the pretreated film layer; and under the action of plasma, the head hydroxyl group of 6-mercapto-1-hexanol can be connected to the surface of the pretreated film layer through van der Waals forces, and the tail thiol of 6-mercapto-1-hexanol forms Au-S bonds with gold nanorods, thereby increasing the adhesion of gold nanorods on the substrate and improving the loading stability. At the same time, through adsorption effects such as electrostatic forces, the loading speed can be increased, the loading capacity is increased, the loading capacity is high and stable, there are more Raman amplification sites, the Raman signal is amplified, thereby enhancing the Raman signal intensity and reducing the interference of fluorescence background.
[0009] Preferably, the specific preparation method of the gold seed in S1 is as follows: Mix 10 mL of a solution of 4-6 mM citric acid, 48-52 mM hexadecyltrimethylammonium bromide, and 0.22-0.28 mM chloroauric acid, stir well, and then add sodium borohydride for reduction treatment to obtain a seed solution. Heat the seed solution in an oil bath at 75-85℃ for 85-95 min until the color turns red. Remove the seed solution. The average gold concentration in the seed solution is 0.22-0.28 mM, and the gold seed is obtained.
[0010] By employing the above technical solution, citric acid is used as a reducing agent and stabilizer, and hexadecyltrimethylammonium bromide is used as a template agent to form micelles, controlling the directional growth of gold nanoparticles. Sodium borohydride rapidly reduces chloroauric acid to generate gold seeds, which are nanospheres. With subsequent oil bath heating, the gold seeds mature, and the color turning red indicates the formation of uniform small-sized gold nuclei, which are the gold seeds. The uniformly grown gold seeds can grow into uniform gold nanorods. The surface of the gold seeds is loaded with the negative charge of citrate ions, and the surface of the gold nanorods is also negatively charged, which can be electrostatically adsorbed onto the surface of the pretreated film, ensuring the loading effect of the SERS substrate and enhancing the Raman signal intensity. Furthermore, hexadecyltrimethylammonium bromide forms a bilayer structure on the surface of the gold seeds, selectively adsorbing onto the gold crystal face through functional groups, inhibiting lateral growth, and promoting the directional deposition of gold seeds along the face into rod-shaped structures, further ensuring the loading effect of the gold nanorods and enhancing the Raman signal intensity.
[0011] Preferably, the specific steps for synthesizing crude gold nanorods using gold seeds in S1 are as follows: Add 0.6-1 g of sodium salicylate and 280-320 μL of AgNO3 aqueous solution to a growth solution containing hexadecyltrimethylammonium bromide (240-260 mL, 7-10 mM) and HAuCl4 (0.6-0.65 mL, 45-54 mM). Mix well for 12-18 min, then add an equal volume of ascorbic acid (0.6-0.65 mL, 80-120 mM). Mix well, then add 10-30 μL of gold seed to the growth solution and shake well to obtain crude gold nanorods.
[0012] By employing the above technical solution, hexadecyltrimethylammonium bromide serves as a structure-directing agent, forming a micelle template. Its hydrophobic chains guide the directional growth of gold seeds along the crystal interface, inhibiting lateral expansion and promoting the formation of rod-like structures. Excessive concentration can easily lead to aggregation, while insufficient concentration can easily result in morphology loss of control. Silver ions in silver nitrate selectively adsorb onto the interface of the growing gold nanorods, inhibiting radial growth, reducing the longitudinal growth energy barrier, and regulating the aspect ratio. Sodium salicylate, as a mild reducing agent and morphology-regulating agent, interacts with the surface of the gold seeds through its carboxyl groups, slowing down the reduction rate, improving the monodispersity of the gold nanorods, and avoiding aggregation and accumulation problems. The weakly reducing form of ascorbic acid enables the slow deposition of gold ions on the surface of the gold seeds. The gold seeds provide uniform nucleation sites, and the slow deposition controls the size of the gold nanorods while ensuring their size uniformity. Gold nanorods can be rapidly and uniformly deposited on the surface of the SERS substrate, thereby enhancing the Raman signal.
[0013] Preferably, the growth length of the crude gold nanorods is 20-100 nm.
[0014] By employing the above technical solution and limiting the size of the gold nanorods' rod-like structure, the Raman signal can be amplified, thereby enhancing the Raman scattering effect.
[0015] Preferably, the specific steps for purifying and preparing gold nanorods in S1 are as follows: After centrifuging to remove some of the supernatant, deionized water was added to make up the difference. This process was repeated 2-4 times to complete the purification.
[0016] By employing the above technical solution, centrifugation removes reaction residues, avoiding interference with the contact loading between gold nanorods and the polyvinylidene fluoride (PVDF) membrane, which could reduce Raman signal intensity. The purified substrate surface exhibits high cleanliness, making it easier for analyte molecules to adsorb onto "hot spot" regions. Repeated centrifugation-resuspending improves the monodispersity of gold nanorods in the aqueous phase, reducing non-specific aggregation. Uniformly dispersed nanorods provide more homogeneous SERS active sites, enhancing signal reproducibility and intensity. Deionized water replenishment regulates the surface charge distribution of the nanorods, enhancing electrostatic interactions with charged analyte molecules and improving molecular enrichment efficiency. The purified gold nanorods adhere rapidly and stably to the PVDF membrane surface, increasing the Raman signal intensity of the SERS substrate.
[0017] Preferably, the specific steps for activating the polyvinylidene fluoride membrane in S2 are as follows: Place a polyvinylidene fluoride membrane on a quartz glass slide, then add 2-5 mL of anhydrous ethanol to activate it for 10-20 min.
[0018] By employing the above technical solution, activating the polyvinylidene fluoride (PVDF) membrane with anhydrous ethanol can impart a microporous structure to the PVDF membrane surface. The PVDF membrane has a microporous structure filled with air. After ethanol treatment, the ethanol, with its lower surface tension than water, easily wets the PVDF membrane surface and penetrates into the micropores, replacing the air in the pores. The ethanol fills the membrane pores and adheres to the membrane surface, making the PVDF membrane surface wet. Water can pass smoothly through the membrane pores, resulting in good water flux at the surface. This transforms the originally hydrophobic PVDF membrane into a temporarily hydrophilic surface, attracting gold nanorods (which are in a composite liquid state). Furthermore, the negative inductive effect of the -CF groups on the PVDF membrane is activated, making them positively charged. Under electrostatic forces, a large number of negatively charged gold nanorods are adsorbed, achieving uniform and dense fixation of the gold nanorods on the PVDF membrane surface. This not only improves adsorption efficiency but also increases the adsorption amount and stability, resulting in a highly active SERS substrate (PVDF-gold nanorod substrate), thereby enhancing the Raman signal.
[0019] Preferably, the specific steps of the plasma cleaning in S2 are as follows: The plasma cleaning time is 1-3 minutes, the power is 180-220W, and the oxygen flow rate is 1.2-1.8L / min.
[0020] By adopting the above technical solution and limiting the conditions of plasma cleaning, the surface etching micropores increase the specific surface area, making it easier to adsorb gold nanorods, and increasing hydrophilicity, thereby further improving the adsorption stability of gold nanorods and enhancing the Raman signal.
[0021] Preferably, the specific steps in step S3 of loading 6-mercapto-1-hexanol and gold nanorods onto the surface of the polyvinylidene fluoride film are as follows: 6-Mercapto-1-hexanol and gold nanorods were mixed evenly at a volume ratio of 1:0.8-1.2, and then dropped onto the surface of a polyvinylidene fluoride membrane. After ion cleaning for 8-12 minutes, the plasma cleaning power was 130-180W and the oxygen flow rate was 1.2-1.8L / min, the loading was completed.
[0022] By adopting the above technical solution, 6-mercapto-1-hexanol is used as a binder to form a sandwich structure of PVDF@6-mercapto-1-hexanol@gold nanorods, thereby increasing the substrate loading. Plasma cleaning catalysis technology is used to efficiently remove impurities on the polyvinylidene fluoride film, catalyze 6-mercapto-1-hexanol to bond the substrate and connect it to the gold nanorods, thereby ensuring the loading and stability of the gold nanorods, and thus enhancing the Raman signal of the SERS substrate.
[0023] Mercapto-1-hexanol is a bifunctional molecule. The terminal thiol group has a strong affinity for gold and can be firmly adsorbed onto the surface of gold nanorods through Au-S bonds. The hydroxyl group at the other end of 6-mercapto-1-hexanol is hydrophilic and can serve as a reaction anchor point. It can also attract and connect to the surface of the pretreated film, thereby further stabilizing the strong loading of gold nanorods on the surface of the pretreated film and enhancing the Raman signal of the SERS substrate.
[0024] 6-Mercapto-1-hexanol was premixed with gold nanorods, allowing 6-mercapto-1-hexanol molecules to form a self-assembled monolayer on the surface of the gold nanorods. This self-assembled monolayer replaced the hexadecyltrimethylammonium bromide on the surface of the gold nanorods, improving the stability of the gold nanorods during subsequent processing and preventing aggregation. The monolayer "decorated" the surface of the gold nanorods with a large number of -OH groups, enhancing the hydrophilicity of the gold nanorods. The finite chain length (C6) of 6-mercapto-1-hexanol meant that when the gold nanorods approached or aggregated in subsequent steps, the monolayer formed a physical barrier, limiting overly close contact between the nanorods and helping to create controllable small gaps, thus further ensuring the parallel alignment of the gold nanorods and enhancing the Raman signal. The dropwise addition facilitated adsorption onto the surface and pores of the pretreated film. Combined with subsequent plasma cleaning, this further improved the hydrophilicity of the polyvinylidene fluoride (PVDF) film surface, enhancing the loading stability and uniformity of the gold nanorods on the pretreated film surface, thereby enhancing the Raman signal and reducing background interference. Secondly, this application provides a method for using a SERS substrate, employing the following technical solution: A method for using a SERS substrate includes the following steps: placing 0.05-0.1g of single-walled carbon nanotubes on the SERS substrate, flattening it with a quartz glass slide, and testing it using a Raman spectrometer; the SERS substrate is prepared using a method for rapidly preparing a SERS substrate with high-load gold nanorods.
[0025] A method for using a SERS substrate includes the following steps: placing 0.1-0.5g of graphite sample on the SERS substrate and testing it using a Raman spectrometer; the SERS substrate is prepared using a rapid method for preparing a SERS substrate with high-load gold nanorods.
[0026] By adopting the above technical solution, when the single-walled carbon nanotubes or graphite being analyzed are adsorbed onto the 6-mercapto-1-hexanol layer or directly close to the gold surface, charge transfer resonance between molecules and metal or between molecules and 6-mercapto-1-hexanol and metal may occur under the action of excitation light, resulting in a change in molecular polarizability and enhancing the Raman scattering cross section, thereby enabling the verification of Raman signal intensity.
[0027] In summary, this application has the following beneficial effects: 1. Using MCH as a binder, a PVDF-MCH-AuNRs sandwich structure is formed, increasing the substrate loading. Plasma cleaning catalysis is used to efficiently remove impurities from PVDF, catalyzing MCH to bond the substrate and connect to AuNRs. Compared with other complex surface coating and multi-step modification methods, this method is simple, allows for single-batch preparation, and uses inexpensive raw materials. Furthermore, the prepared SERS substrate has a high AuNRs loading and numerous Raman amplification sites. By amplifying the Raman signal through AuNRs, the signal intensity of Raman testing is significantly improved, and interference from fluorescence background is reduced.
[0028] 2. High-density and high-content gold nanorods loaded on the substrate surface can form a large number of nanoscale gaps, exciting strong local surface plasmon resonances. These gaps can localize and amplify the incident light by 10⁻⁶. 6 -10 8 The high loading capacity significantly enhances the Raman scattering signal of the adsorbed molecules; and the high loading capacity ensures that the number of hot spots per unit area is maximized, increasing the probability of the target molecules being excited and achieving ultrasensitive detection.
[0029] 3. The uniform size and high loading of gold nanorods facilitate the formation of parallel alignment structures on the surface of polyvinylidene fluoride films. The longitudinal electromagnetic field superposition effect generated between the parallel nanorods further enhances the Raman signal. Attached Figure Description
[0030] Figure 1 This is a TEM image of the 20nm gold nanorods in this application; Figure 2 This is the ultraviolet spectrum of the gold nanorods in Example 1 of this application; the inset is of a solution. Figure 3 These are Raman test results for Application Example 1, Control Groups 1 and 2 of this application; Figure 4 These are the Raman test results of Application Example 4 and Control Groups 3 and 4 in this application; Figure 5 The images show the Raman test results of comparative application example 1 and control groups 5, 6, 7, and 8 of this application. Detailed Implementation
[0031] The present application will be further described in detail below with reference to the embodiments and accompanying drawings. Example
[0032] Example 1: A method for rapidly preparing a SERS substrate with highly loaded gold nanorods: S1. In a 20 mL Erlenmeyer flask, add a mixed solution of 10 mL of 5 mM citric acid, 50 mM hexadecyltrimethylammonium bromide, and 0.25 mM chloroauric acid (water as solvent), stir until homogeneous, then add 0.25 mL of NaBH4 (25 mM) for rapid reduction. Prepare a seed solution at room temperature (25 °C). The mixture changes from light yellow to brown, indicating the formation of gold seeds. After 2 min, heat the seed solution in an oil bath at 80 °C for 90 min, stirring gently until homogeneous. The color gradually changes from brown to red. Remove the heat-treated seed solution from the oil bath and store at room temperature. The average gold concentration in the seed solution is 0.25 mM, yielding gold seeds. Add 250 mL of hexadecyltrimethylammonium bromide (8 mM) and 0.625 mL of HAuCl4 (250 mL of NaBH4) to the solution. The gold nanorods were immersed in a 20°C constant temperature bath with deionized water as the solvent in the growth solution (50 mM). Then, 0.8 g of sodium salicylate and 300 μL of 0.01 M AgNO3 aqueous solution were added. After 15 min, an equal volume of ascorbic acid (0.625 mL, 100 mM) was added, and the mixture was shaken by hand until it became colorless. 20 μL of gold seed was added to the growth solution, and the mixture was shaken well and incubated undisturbed at 20°C overnight to obtain crude gold nanorods with an average length of 60 nm. The crude gold nanorods were centrifuged at 8000 rpm for 30 min. A portion of the supernatant was removed using a pipette, and the supernatant was replenished with deionized water. This process was repeated three times to complete the purification and obtain gold nanorods (AuNRs). The gold nanorods were stored in PE tubes for later use. S2. Place a 5cm-sized object on a quartz glass slide. 2The polyvinylidene fluoride (PVDF) membrane was activated by adding 4 mL of anhydrous ethanol for 15 min. The quartz glass slide loaded with PVDF was then placed in a plasma cleaner (model PDC-MG) for 2 min with the power set to 200 W and the oxygen flow rate set to 1.5 L / min to remove impurities from the PVDF surface, thus forming a pretreated film layer on the quartz glass slide. S3. Take 10 mL of 0.1 M 6-mercapto-1-hexanol (MCH) and 10 mL of AuNRs and mix at room temperature. Stir for 10 min to obtain a mixture. Drop the mixture onto the surface of the pretreated film on a quartz glass slide and treat it with a plasma cleaner for 10 min. The power is set to 150 W and the oxygen flow rate is 1.5 L / min. Remove the quartz glass slide, wash away the unreacted reagents with deionized water, and dry it in an oven at 45 °C to obtain the PVDF-MCH-AuNRs composite SERS substrate.
[0033] Example 2: The difference between this example and Example 1 is that: S1. In a 20 mL Erlenmeyer flask, add a mixed solution of 10 mL of 4 mM citric acid, 48 mM hexadecyltrimethylammonium bromide, and 0.22 mM chloroauric acid (water as solvent), stir until homogeneous, then add 0.25 mL of NaBH4 (25 mM) for rapid reduction. Prepare the seed solution at room temperature (25°C). The mixture changes from light yellow to brown, indicating the formation of gold seeds. After 2 min, heat the seed solution in an oil bath at 75°C for 95 min, stirring gently until homogeneous. The color gradually changes from brown to red. Remove the heat-treated seed solution from the oil bath and store at room temperature. The average gold concentration in the seed solution is 0.22 mM, yielding gold seeds. Add 240 mL of hexadecyltrimethylammonium bromide (10 mM) and HAuCl4 (… The growth solution (0.6 mL, 54 mM) was immersed in a 20°C constant temperature bath with deionized water as the solvent. Then, 0.6 g of sodium salicylate and 280 μL of 0.01 M AgNO3 aqueous solution were added. After 12 minutes, an equal volume of ascorbic acid (0.6 mL, 120 mM) was added, and the mixture was shaken by hand until it became colorless. 10 μL of gold seed was added to the growth solution, and the mixture was shaken well and incubated undisturbed overnight at 20°C to obtain crude gold nanorods with an average length of 20 nm. The crude gold nanorods were centrifuged at 8000 rpm for 30 min. A portion of the supernatant was removed using a pipette, and the supernatant was replenished with deionized water. This process was repeated twice to complete the purification and obtain the gold nanorods. The gold nanorods were stored in PE tubes for later use. S2. Place a 2cm-sized object on a quartz glass slide. 2The polyvinylidene fluoride membrane was activated by adding 2 mL of anhydrous ethanol for 20 min. The quartz glass slide loaded with PVDF was then placed in a plasma cleaner (model PDC-MG) for 1 min with the power set to 220 W and the oxygen flow rate set to 1.2 L / min to remove impurities from the PVDF surface, thus forming a pretreated film layer on the quartz glass slide. S3. Take 10 mL of 0.1 M 6-mercapto-1-hexanol (MCH) and 8 mL of AuNRs and mix at room temperature. Stir for 10 min to obtain a mixture. Drop the mixture onto the surface of the pretreated film on a quartz glass slide and treat it with a plasma cleaner for 8 min at a power of 130 W and an oxygen flow rate of 1.8 L / min. Remove the quartz glass slide, wash away unreacted reagents with deionized water, and dry it in a 45 °C oven to obtain a PVDF-MCH-AuNRs composite SERS substrate.
[0034] Example 3: The difference between this example and Example 1 is that: S1. In a 20 mL Erlenmeyer flask, add a mixed solution of 10 mL of 6 mM citric acid, 52 mM hexadecyltrimethylammonium bromide, and 0.28 mM chloroauric acid (water as solvent), stir until homogeneous, then add 0.25 mL of NaBH4 (25 mM) for rapid reduction. Prepare the seed solution at room temperature (25°C). The mixture changes from light yellow to brown, indicating the formation of gold seeds. After 2 min, heat the seed solution in an oil bath at 85°C for 85 min, stirring gently until homogeneous. The color gradually changes from brown to red. Remove the heat-treated seed solution from the oil bath and store at room temperature. The average gold concentration in the seed solution is 0.28 mM, yielding gold seeds. Add 260 mL of hexadecyltrimethylammonium bromide (10 mM) and HAuCl4 (0... The growth solution (0.65 mL, 45 mM) was immersed in a 20°C constant temperature bath with deionized water as the solvent. Then, 1 g of sodium salicylate and 320 μL of 0.01 M AgNO3 aqueous solution were added. After 18 min, an equal volume of ascorbic acid (0.65 mL, 80 M) was added, and the mixture was shaken by hand until it became colorless. 30 μL of gold seed was added to the growth solution, and the mixture was shaken well and incubated undisturbed overnight at 20°C to obtain crude gold nanorods with an average length of 100 nm. The crude gold nanorods were centrifuged at 8000 rpm for 30 min. A portion of the supernatant was removed using a pipette, and the supernatant was replenished with deionized water. This process was repeated 4 times to complete the purification and obtain the gold nanorods. The gold nanorods were stored in PE tubes for later use. S2. Place a 9cm-sized object on a quartz glass slide. 2The polyvinylidene fluoride membrane was activated by adding 5 mL of anhydrous ethanol for 10 min. The quartz glass slide loaded with PVDF was then placed in a plasma cleaner (model PDC-MG) for 3 min with the power set to 180 W and the oxygen flow rate set to 1.8 L / min to remove impurities from the PVDF surface and form a pretreated film layer on the quartz glass slide. S3. Take 10 mL of 0.1 M 6-mercapto-1-hexanol (MCH) and 12 mL of AuNRs and mix at room temperature. Stir for 10 min to obtain a mixture. Drop the mixture onto the surface of the pretreated film on a quartz glass slide and treat it with a plasma cleaner for 12 min. The power is set to 180 W and the oxygen flow rate is 1.8 L / min. Remove the quartz glass slide, wash away the unreacted reagent with deionized water, and dry it in an oven at 45 °C to obtain the PVDF-MCH-AuNRs composite SERS substrate.
[0035] Application examples Application Example 1: A method for using a SERS substrate: 0.1 g of single-walled carbon nanotubes were placed on a SERS substrate and flattened with another clean quartz glass slide in a cross shape. The test was performed using a 532 nm Raman spectrometer (model: Thermo Fisher DRx3). The test parameters were spot scan, laser power 2.0 Mw, exposure time 10 s, and 3 scans. The SERS substrate was prepared using the method described in Example 1 for rapidly preparing a SERS substrate with high-load gold nanorods.
[0036] Application Example 2: The difference between this application example and Application Example 1 is that: 0.05 g of single-walled carbon nanotubes were placed on a SERS substrate and flattened with another clean quartz glass slide in a cross shape. The test was performed using a 532 nm Raman spectrometer (model: Thermo Fisher DRx3). The test parameters were spot scan, laser power 2.0 Mw, exposure time 10 s, and 3 scans. The SERS substrate was prepared using the method described in Example 2 for rapidly preparing a SERS substrate with high-load gold nanorods.
[0037] Application Example 3: The difference between this application example and Application Example 1 is that: 0.08 g of single-walled carbon nanotubes were placed on a SERS substrate and flattened with another clean quartz glass slide in a cross shape. The test was performed using a 532 nm Raman spectrometer (model: Thermo Fisher DRx3). The test parameters were spot scan, laser power 2.0 Mw, exposure time 10 s, and 3 scans. The SERS substrate was prepared using the method described in Example 3 for rapidly preparing a SERS substrate with high-load gold nanorods.
[0038] Application Example 4: A method for using a SERS substrate: 0.3g of graphite sample was placed on the SERS substrate and flattened with another clean quartz glass slide in a cross shape. The test was performed using a 532nm Raman spectrometer (model: Thermo Fisher DRx3). The test parameters were spot scan, laser power 2.0Mw, exposure time 10s, and 3 scans. The SERS substrate was prepared using the method described in Example 1 for rapidly preparing a SERS substrate with high-load gold nanorods.
[0039] Application Example 5: The difference between this application example and Application Example 4 is that: A 0.1g graphite sample was placed on a SERS substrate and flattened with another clean quartz glass slide in a cross shape. The sample was tested using a 532nm Raman spectrometer (model: Thermo Fisher DRx3). The test parameters were spot scan, laser power 2.0Mw, exposure time 10s, and 3 scans. The SERS substrate was prepared using the method described in Example 1 for rapidly preparing a SERS substrate with high-load gold nanorods.
[0040] Application Example 6: The difference between this application example and Application Example 4 is that: 0.5g of graphite sample was placed on the SERS substrate and flattened with another clean quartz glass slide in a cross shape. The test was performed using a 532nm Raman spectrometer (model: Thermo Fisher DRx3). The test parameters were spot scan, laser power 2.0Mw, exposure time 10s, and 3 scans. The SERS substrate was prepared by the method described in Example 1 for rapidly preparing a SERS substrate with high-load gold nanorods.
[0041] Comparative application examples Comparative Application Example 1: Detection of a type of polystyrene: Take 0.1g of polystyrene sample and place it on the SERS substrate prepared in Example 1. Use 532nm wavelength Raman spectroscopy for testing. The test parameters are: laser power 1.0mW, exposure time 10s, and number of scans 10.
[0042] Performance testing 1. Raman signal intensity detection For Application Example 1 (denoted as PVDF@MCH@AuNRs), two control groups were prepared, namely control group 1 and control group 2.
[0043] Control group 1 (denoted as PVDF): 0.1g of single-walled carbon nanotubes were placed on a polyvinylidene fluoride film substrate and flattened with another clean quartz glass slide in a cross shape. The Raman spectrometer (model: Thermo Fisher DRx3) at 532nm was used for testing. The test parameters were spot scan, laser power 2.0Mw, exposure time 10s, and 3 scans. The Raman signal was measured.
[0044] Control group 2 (denoted as PVDF@MCH): 0.1g of single-walled carbon nanotubes were placed on the PVDF@MCH substrate and flattened with another clean quartz glass slide in a cross shape. The Raman spectrometer (model: Thermo Fisher DRx3) at 532nm was used for testing. The test parameters were spot scan, laser power 2.0Mw, exposure time 10s, and 3 scans. The Raman signal was measured.
[0045] The Raman signal test results of Application Example 1, Control Group 1, and Control Group 2 are as follows: Figure 3 As shown, the Raman signals of the PVDF substrate and PVDF@MCH substrate are weak, indicating the loss of the unique respiratory vibration peak of SWNTs; while the SERS substrate prepared in this application has a sharp peak and high intensity, with RBM appearing at 187 cm⁻¹. -1 .
[0046] For application example 4 (denoted as PVDF@MCH@AuNRs), two control groups were prepared, namely control groups 3 and 4.
[0047] Control group 3 (denoted as PVDF): 0.3g of graphite sample was placed on a polyvinylidene fluoride film substrate and flattened with another clean quartz glass slide in a cross shape. The Raman spectrometer (model: Thermo Fisher DRx3) at 532nm was used for testing. The test parameters were spot scan, laser power 2.0Mw, exposure time 10s, and 3 scans. The Raman signal was measured.
[0048] Control group 4 (denoted as PVDF@MCH): 0.3g of graphite sample was placed on the PVDF@MCH substrate and flattened with another clean quartz glass slide in a cross shape. The Raman spectrometer (model: Thermo Fisher DRx3) at 532nm was used for testing. The test parameters were spot scan, laser power 2.0Mw, exposure time 10s, and 3 scans. The Raman signal was measured.
[0049] The PVDF@MCH substrate preparation method described above is as follows: Place a 5cm² substrate on a quartz glass slide. 2The polyvinylidene fluoride (PVDF) membrane was activated with 4 mL of anhydrous ethanol for 15 min. The PVDF-loaded quartz glass slide was then treated in a plasma cleaner (model PDC-MG) for 2 min at a power of 200 W and an oxygen flow rate of 1.5 L / min to remove impurities from the PVDF surface, forming a pretreated film layer on the quartz glass slide. 10 mL of 0.1 M 6-mercapto-1-hexanol (MCH) was added to the surface of the pretreated film layer on the quartz glass slide, and the slide was treated with a plasma cleaner for 10 min at a power of 150 W and an oxygen flow rate of 1.5 L / min. The quartz glass slide was then removed, and unreacted reagents were washed away with deionized water. The slide was then dried in a 45 °C oven to obtain the finished substrate.
[0050] The Raman signal test results of Application Example 4, Control Group 3, and Control Group 4 are as follows: Figure 4 As shown, the Raman signals of the PVDF substrate and the PVDF@MCH substrate are relatively weak; while the SERS substrate prepared in this application has sharp peaks and high intensity.
[0051] For comparative application example 1 (denoted as PVDF@MCH@AuNRs), four control groups were prepared, namely control groups 5, 6, 7, and 8.
[0052] The control group 5 was denoted as (Ag): 0.1g of polystyrene sample was placed on a gold-sprayed quartz glass slide and Raman test was performed using a wavelength of 532nm. The test parameters were: laser power 1.0mW, exposure time 10s, and 10 scans. The Raman signal was measured.
[0053] Control group 6 (hereinafter referred to as Patent A): The finished product prepared by the method of Example 1 using the Chinese invention patent document with publication number CN118688176A in the prior art was used to detect the Raman signal.
[0054] Control group 7 (hereinafter referred to as Patent B): The finished product prepared by the method of Example 1 using the Chinese invention patent document with publication number CN112881360A in the prior art was used to detect the Raman signal.
[0055] Control group 8 (hereinafter referred to as Patent C): The finished product prepared by the method of Example 1 using the Chinese invention patent document with publication number CN113834804B in the prior art was used to detect the Raman signal.
[0056] The Raman signal test results of Application Example 1, Control Group 5, Control Group 6, Control Group 7, and Control Group 8 are compared as follows: Figure 5As shown, the signal intensity of the polystyrene sample on the prepared substrate is slightly higher than that of the gold sputtering substrate, indicating that the signal amplification effect of the prepared substrate is similar to that of the Au / Ag coating. In the SERS substrate prepared in this application, MCH acts as a "binder," resulting in more Raman-active molecules being enriched on the flat substrate. The test signal of this application is much higher than that of patents A / B / C, indicating that the finished SERS substrate has the advantages of high Raman signal intensity and reduced fluorescence background interference.
[0057] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A method for rapidly preparing a SERS substrate with highly loaded gold nanorods, characterized in that, Includes the following steps: S1. Gold seeds were prepared by compounding citric acid, hexadecyltrimethylammonium bromide and chloroauric acid, and then crude gold nanorods were prepared by gold seed synthesis and purified to obtain gold nanorods; S2. The polyvinylidene fluoride membrane is activated with ethanol and cleaned by plasma to obtain a pretreated membrane layer. S3. Load 6-mercapto-1-hexanol and gold nanorods onto the surface of the pretreated film, and then dry it to obtain the finished product.
2. The method for rapidly preparing a SERS substrate with highly loaded gold nanorods according to claim 1, characterized in that: The specific preparation method of the gold seed in S1 is as follows: Mix 10 mL of a solution of 4-6 mM citric acid, 48-52 mM hexadecyltrimethylammonium bromide, and 0.22-0.28 mM chloroauric acid, stir well, and then add sodium borohydride for reduction treatment to obtain a seed solution. Heat the seed solution in an oil bath at 75-85℃ for 85-95 min until the color turns red. Remove the seed solution. The average gold concentration in the seed solution is 0.22-0.28 mM, and the gold seed is obtained.
3. The method for rapidly preparing a SERS substrate with highly loaded gold nanorods according to claim 1, characterized in that, The specific steps for synthesizing crude gold nanorods using gold seeds in S1 are as follows: Add 0.6-1 g of sodium salicylate and 280-320 μL of AgNO3 aqueous solution to a growth solution containing hexadecyltrimethylammonium bromide (240-260 mL, 7-10 mM) and HAuCl4 (0.6-0.65 mL, 45-54 mM). Mix well for 12-18 min, then add an equal volume of ascorbic acid (0.6-0.65 mL, 80-120 mM). Mix well, then add 10-30 μL of gold seed to the growth solution and shake well to obtain crude gold nanorods.
4. The method for rapidly preparing a SERS substrate with highly loaded gold nanorods according to claim 3, characterized in that, The growth length of the crude gold nanorods is 20-100 nm.
5. The method for rapidly preparing a SERS substrate with highly loaded gold nanorods according to claim 1, characterized in that, The specific steps for purifying and preparing gold nanorods in S1 are as follows: After centrifuging to remove some of the supernatant, deionized water was added to make up the difference. This process was repeated 2-4 times to complete the purification.
6. The method for rapidly preparing a SERS substrate with highly loaded gold nanorods according to claim 1, characterized in that, The specific steps for activating the polyvinylidene fluoride membrane in S2 are as follows: Place a polyvinylidene fluoride membrane on a quartz glass slide, then add 2-5 mL of anhydrous ethanol to activate it for 10-20 min.
7. The method for rapidly preparing a SERS substrate with highly loaded gold nanorods according to claim 1, characterized in that, The specific steps of the plasma cleaning in S2 are as follows: The plasma cleaning time is 1-3 minutes, the power is 180-220W, and the oxygen flow rate is 1.2-1.8L / min.
8. The method for rapidly preparing a SERS substrate with highly loaded gold nanorods according to claim 1, characterized in that, The specific steps in S3 for loading 6-mercapto-1-hexanol and gold nanorods onto the surface of the polyvinylidene fluoride membrane are as follows: 6-Mercapto-1-hexanol and gold nanorods were mixed evenly at a volume ratio of 1:0.8-1.2, and then dropped onto the surface of a polyvinylidene fluoride membrane. After ion cleaning for 8-12 minutes, the plasma cleaning power was 130-180W and the oxygen flow rate was 1.2-1.8L / min, the loading was completed.
9. A method of using a SERS substrate, characterized in that, Includes the following steps: Take 0.05-0.1g of single-walled carbon nanotubes and place them on a SERS substrate. Flatten them with a quartz glass slide and test them using a Raman spectrometer. The SERS substrate was prepared using the method for rapidly preparing a SERS substrate with high-load gold nanorods according to any one of claims 1-8.
10. A method of using a SERS substrate, characterized in that, Includes the following steps: Take 0.1-0.5g of graphite sample and place it on a SERS substrate, then perform Raman spectroscopy. The SERS substrate was prepared using the method for rapidly preparing a SERS substrate with high-load gold nanorods according to any one of claims 1-8.
Citation Information
Patent Citations
SERS substrate based on PVDF film, Raman detection system based on substrate and application of system
CN112881360A
A method for constructing and applying flexible surface-enhanced Raman substrates
CN113834804B
Gold nanosphere self-assembled superlattice surface enhanced Raman spectrum substrate as well as preparation method and application thereof
CN118688176A